Accumulation of root-stubble residues and nutrients in feed crop rotations - A. K. Svechnikov (Аграрная наука Евро-Северо-Востока)
From 2001 to 2018 in Mari El Republic six-field fodder crop rotations including 1-3 fields of legume-cereal grasses were studied. The amount of plowed root-crop residues and nutrients entering the soil was assessed at different levels of minerals application (N60P60K60 and N90P90K90 in the 1st and 2 nd rotations, N60P60K60 и P60K60 in the 3rd rotation). During the research the total nitrogen content in sod-podzolic soil increased from 0.15% to 0.28%, the humus content raised from 1.82% to 2.53%. The largest amount of root-crop residues nutrients was plowed into 0 -20 cm soil layer during the fodder crop rotation at the 1-year use of the perennial grasses. On the average, it received 35.2 t/ha of dry matter, 560 kg/ha of nitrogen, 231 kg/ha of phosphorus and 338 kg/ha of potassium over 3 rotations. An increase in supply of soils with nitrogen and humus in the 3rd rotation raised the plant residues and nutrients accumulation to 49.9 t/ha, 821 kg/ha, 321 kg and 496 kg/ha, respectively. No significant differences were found between the fertilization backgrounds. In the structure of studied crop rotations cloveralfalfa-timothy grass mixture has made the greatest contribution to in the replenishment of nutrient elements by plowing up the root-crop residues: 10.1 tons of dry matter, 199 kg of nitrogen, 89 kg of phosphorus and 115 kg/ha of potassium. Using postcut mustard after winter rye provided almost the same amount of plowed root-crop residues as clover-alfalfa-timothy grass mixture.Conflict of interest: the authors stated that there was no conflict of interest.